The Brazilian Midwest lateritic domains: Regolith features and dynamic. (October 2022) - Castro, Rodrigo Tokuta; Horbe, Adriana Maria Coimbra; Cherem, Luis Felipe Soares
Abstract: Intracontinental deformations cause the uplift of erosive surfaces and are consequence of lithosphere destabilization processes in cratonic domains. The Atlantic Ocean opening influenced processes 2000 km away from the coast with reflections in the regolith. The Brazilian Midwest regolith is characterised by a stepwise landscape of highlands, mountains, plateaus, inselbergs, canyons, and lowlands that form four morphostratigraphic surfaces. Surface 1 is sustained by quartzite mountains. Surfaces 2 and 3 are mantled by ferruginous lateritic duricrusts. The duricrusts in surface 2 are quartz-hematitic, hardened, columnar, reddish-pink to yellowish-red, have protonodular, fragmental, and pisolitic textures, and reach up to 3 m thick, whereas the duricrusts in surface 3 are more friable, quartz-goethitic, columnar, yellowish-red to orangish-yellow, have a vermiform texture with bioturbated micro-aggregated clay-ferruginous matrix, reaching up to 2 m thick. Surface 4 includes the lower alluvial plains. The purpose of this study was to understand the formation of these regolith surfaces, their relationships, the impact of the lateritic dynamic, and the continental influences as a landscape-shaping agent. The area was studied using SRTM images, swath profiles, and the Roughness Concentration Index, as well as fieldwork control, textures, mineralogy, and geochemistry analysis. Surface 1 marks the regional erosional event, while surfaces 2 and 3 mark two stable well-drained ferruginization weathering episodes and a seasonal drier to humid climate change. Surface 4 sculpts the lowlands. These regolith sequential landforms surfaces were produced in a complex landscape process modelled by an extensive erosional regime as a result of tectonic movements during the Atlantic Ocean evolution evolution and tropical weathering climate since the Neogene, as indicated by the lateritic duricrusts features (textures, mineral, and chemical composition). This landscape is younger than expected for Archean to Paleozoic terrains subjected to tropical weathering, dating back at least to the Paleogene, the age of the majority of older lateritic duricrusts in Brazil and around the world. These younger morphostratigraphic surfaces in cratonic domains, as well as the geological processes involved in tectonic and climate influence, had significant implications for the Brazilian South American Platform regolith. Graphical abstract: Image 1 Highlights: Parts of the Brazilian Midwest were uplifted impacting on the regolith features. The Brazilian Midwest regolith form four morphostratigraphic surfaces, two surfaces are mantled by distinct extensive ferruginous lateritic duricrusts. There is an absence of lateritic bauxites and only hydrothermal bauxites occur, the features of the lateritic duricrust indicate a forming only since the Neogene.